Analysis of Japanese Defeats at The Battle of Midway in 1942 - A. Fauzan; Rudi Sutanto; Ansori Zaini (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
After achieving success in the attack on the Navy base at Pearl Harbor on December 7h 1941, the Japanese Empire felt that it had still not completed its goal of crippling the strength of the United States Navy in the Pacific region. This was because the United States and its allies were considered to be a serious threat to Japan's ambitions to dominate Greater Asia. This was done as a continuation of Japan's plan to attack the base and its fleet of warships and fighter planes at Athol Midway. This was preceded by strategic efforts and deceptive tactics to create threatening conditions on the Aleutian islands, it was hoped that this would lead the United States to be trapped in the area, and then they would be attacked by the Japanese Navy fleet in full force. However, what happened was just the opposite, the naval battle at Midway on June 4-7th 1942 resulted in huge defeats and losses for the Japanese Empire, where four aircraft carriers, fighter planes, and several warships were sunk, as well as many crew members and pilots. who died. Meanwhile, on the United States side, an aircraft carrier and several warships were sunk and damaged and many soldiers died. The purpose of writing this article is to use the history of the naval battle at Midway as a very valuable lesson in developing war strategy planning, especially in maritime defense strategies, which can be applied by the Indonesian Navy in the present and the future. The research method used is a qualitative method with a literature approach regarding the history of naval battles in general, including the battle at Midway. Meanwhile, the output of this article is addressed to the Ministry of Defense of the Republic of Indonesia as input regarding the importance of a mature strategy in the National Defense Strategy at sea